Atividade antimicrobiana de Lactobacillus acidophilus, contra microrganismos patogênicos veiculados por alimentos - Pereira, Valeria Garcia [UNESP]; Heman Castro Gomez, Raul Jorge (Universidade Estadual de Londrina (UEL), 2007)
The antimicrobial activity of a commercial probiotic culture, Lactobacillus acidophilus (La5), was tested against two foodborne pathogens, Escherichia coli and Staphylococcus aureus. The antagonistic effect of the probiotic culture in vitro was performed by applying both Multilayer Agar Plate and Agar Well Diffusion methods. The results indicated that the inhibitory substance present on 72 hours culture broth supernatant was extracellular and diffusible. The incubation period of the lactic acid bacteria on MRS Broth, at 3 7 degrees C in aerobic conditions, for the highest lactic acid production (1,08 g/%) was 72 hours, which gave a minimum pH value of the supernatant (3,90) and the best inhibition results by the Well Diffusion Agar Assay, showing inhibition zone diameters of 14,75mm and 15,0mm for E. coli and S. aureus, respectively. The inhibitor compound was not sensitive to proteolytic enzyme and freezing, but was totally inactivated when the supernatant was neutralized with NaOH 1 N solution. The results suggest that the inhibitory activity was due to the lactic acid concentration and the low pH of the probiotic culture broth.
Antimicrobial activity of Lactobacillus acidophilus against foodborne pathogens
Keywords: antimicrobial activity; Lactobacillus acidophilus; lactic acid; probiotic culture